2014
DOI: 10.1016/j.appet.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Are diet-specific compensatory health beliefs predictive of dieting intentions and behaviour?

Abstract: 1Compensatory health beliefs (CHBs) -beliefs that an unhealthy behaviour can be 2 compensated for by healthy behaviour -are hypothesised to be activated automatically 3 to help people resolve conflicts between their desires (e.g. eat chocolate) and their long-4 term goals (e.g. dieting). The aim of the present research was to investigate diet-5 specific CHBs within the context of a theoretical framework, the Health Action Process 6 Approach (HAPA), to examine the extent to which diet-specific CHBs contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
47
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 24 publications
9
47
1
1
Order By: Relevance
“…Interestingly, CHBs positively predicted intentions for IWCD with high-risk perception, corroborating Radtke et al (2014)'s observations. According to this study, CHBs may act as a motivator at an early stage of the health behaviour change process, where risk perceptions arise as a starting point.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Interestingly, CHBs positively predicted intentions for IWCD with high-risk perception, corroborating Radtke et al (2014)'s observations. According to this study, CHBs may act as a motivator at an early stage of the health behaviour change process, where risk perceptions arise as a starting point.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, previous studies reported low scale homogeneity (e.g., α = .44 Radtke et al, 2014). One reason could be that CHBs scales aggregated beliefs about different compensatory behaviours (e.g., unhealthy diet may be compensated by skipping main dish, or by being physically active, Radtke et al, 2014), which is problematic because they may differ in several respects (e.g., required effort, perceived efficacy, McEachan, Lawton, & Conner, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal tenets of the HAPA, and in particular the distinction between motivation and volition, have been supported across a variety of health behaviours, including physical activity (Perrier et al 2012;Hattar, Pal, and Hagger 2016), healthy eating (Radtke et al 2014), smoking cessation (Radtke et al 2012), alcohol consumption (Murgraff et al 2003) and in chronic illness and disability (Schwarzer et al 2011). To date, however, the HAPA model has not been applied in the domain of hearing health care.…”
Section: Introductionmentioning
confidence: 99%
“…This holds true even when behaviour‐specific social cognitions (e.g., outcome expectancies, self‐efficacy) are accounted for. However, CHBs were not found to add to the prediction of behaviour when investigated within the framework of the HAPA (Berli et al ., ; Radtke, Kaklamanou, Scholz, Hornung, & Armitage, ; Radtke et al ., ; Schwarzer, ). Based on these findings, we were tested whether CHBs were negatively associated with physical activity intentions (Berli et al ., ) and self‐regulatory strategies.…”
Section: Introductionmentioning
confidence: 99%